Heterogeneous Weathering Process of Lunar Regolith Revealed by Polarimetric Attributes Analysis of Chang'E‐4 Lunar Penetrating Radar Data Acquired During the Yutu‐2 Turnings. Issue 13 (6th July 2022) - Zhou, Haoqiu; Feng, Xuan; Ding, Chunyu; Dong, Zejun; Liu, Cai; Liang, Wenjing
Abstract: This paper provides analyses to quantify the maturity of regolith within 24 m depth using a novel polarimetric attributes analysis of lunar penetrating radar (LPR) data. The results demonstrate that LPR signals were mainly from subsurface rock fragments of different sizes and were rarely from strata interfaces. The averages and ranges of maturities for the near‐surface (0–2 m), the fine‐grained regolith (2–12 m), and the coarse‐grained ejecta (12–24 m) are 68.98% (0%–99.82%), 82.61% (41.52%–96.56%), and 72.33% (5.91%–96.66%), respectively. Local regions with anomalously low maturities on the lunar surface may be due to the dense materials formed by local impacts or the rock fragments from distal impacts; a newly discovered sandwich structure with low maturity at a depth between 12 and 18 m is formed by the heterogeneous weathering in a paleo‐crater. Based on these new insights, we infer a heterogeneous weathering process of the regolith. Plain Language Summary: The entire lunar surface is considered to be covered by a layer of regolith. The study of regolith weathering degree almost focused on the near‐surface because the traditional techniques cannot detect the regolith at large depths. The Chang'E‐4 lunar penetrating radar (LPR) can detect the regolith structure within dozens of meters depth. However, previous publication of LPR results only use the macro layering model to interpret the regolith structure. This study innovatively extracts new properties from the LPR data acquired while the rover was turning and estimated the quantitative maturity of regolith within ∼24 m depth at lunar farside. We found that the LPR can mainly detect the subsurface rock fragments that survived weathering and rarely the interfaces of strata because the materials of different strata are mixed at interfaces and make it gradational. Our results also reveal the spatial difference of weathering in the regolith. We investigate the formations and material compositions of several interesting regions with unusual weathering degrees. Based on these new insights, we establish a model to illustrate the weathering process of the regolith at the CE‐4 landing site. Key Points: We quantify the maturity of the lunar regolith within 24 m depth by analyzing the lunar penetrating radar (LPR) data acquired during the rover turnings LPR signals were mainly from subsurface rock fragments of different sizes and were rarely from strata interfaces Inferring the heterogeneous weathering process by comprehensively investigating the regions with anomalous maturities in the regolith